Field evaluation of electrophysiologically-active dung volatiles as chemical lures for trapping of dung beetles - Nisansala N. Perera; Russell A. Barrow; Paul A. Weston; Leslie A. Weston; Geoff M. Gurr (Scientific Reports, 2024)
Abstract Dung beetles are economically important beneficial insects that process dung. To locate this source, they use volatile organic compounds (VOCs). The objectives of the study were to evaluate the attractiveness of ten electrophysiologically-active dung volatiles (phenol, skatole, indole, p-cresol, butanone, butyric acid, eucalyptol, dimethyl sulphide, dimethyl disulphide, and toluene) to dung beetles in the field and to investigate how the composition of volatile blends influences efficacy as lures for use in traps. Six combinations of the compounds were compared with field collected cattle dung bait and a negative control, across three seasons. Both dung and synthetic baits captured all exotic dung beetle species present in the study area. A six-compound mix (M1), comprising major dung volatiles, served as an attractive chemical mixture. The addition of dimethyl sulphide, dimethyl disulphide (M2) and toluene (M4) enhanced attractancy of M1 for dung beetles, while eucalyptol (M3) decreased the attractancy. The degree of attraction by various dung beetle species to synthetic baits varied, but baits proved to be effective, especially for summer trapping. The trap design used in this study presented a convenient and practical way to sample dung beetle and other associated scarabs from open pastures. The attraction of introduced dung beetle species to synthetic baits is documented here for the first time in Australia. In addition, necrophagous Omorgus sp. is reported here for the first time to be attracted to synthetic baits. They showed a significant attraction to the mixture containing dimethyl sulphide and dimethyl disulphide (M2). The current study represents a promising first step towards formulating a synthetic chemical lure for dung beetles, offering a consistent, standardised, and bio-secure trapping method compared to use of naturally occurring dung baits, especially as a multi-species lure.